Balancing Demand and Supply for Veterans' Health Care A Summary of Three RAND Assessments Conducted Under the Veterans Choice Act - Health, RAND (RAND Corporation, 2016)
This summary presents results from RAND's assessments of veteran demographics and health care needs, the health care capabilities of the Veteran's Administration (VA), and authorities and mechanisms for purchasing care. It also offers recommendations for improving the match between veterans' needs and VA's capabilities, including VA's ability to purchase necessary care from the private sector.